2009
DOI: 10.1007/s11104-009-0165-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the variability in soybean nitrogen fixation across agroecosystems

Abstract: Legume-based cropping systems have the potential to internally regulate N cycling due to the suppressive effect of soil N availability on biological nitrogen fixation. We used a gradient of endogenous soil N levels resulting from different management legacies and soil textures to investigate the effects of soil organic matter dynamics and N availability on soybean (Glycine max) N 2 fixation. Soybean N 2 fixation was estimated on 13 grain farm fields in central New York State by the 15 N natural abundance metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
84
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 66 publications
9
84
0
Order By: Relevance
“…The similar data were obtained when crops growth at specific landscape positions is influenced by several interacting hill slope process across a typical soil arena (Schipanski et al 2010;Snapp and Kravchenko, 2015;Russenes et al 2016). Influence of landscape position and terrain attributes an annual crop yield has been studied.…”
Section: Introductionsupporting
confidence: 52%
“…The similar data were obtained when crops growth at specific landscape positions is influenced by several interacting hill slope process across a typical soil arena (Schipanski et al 2010;Snapp and Kravchenko, 2015;Russenes et al 2016). Influence of landscape position and terrain attributes an annual crop yield has been studied.…”
Section: Introductionsupporting
confidence: 52%
“…The intercropping of gliricidia, maize, and cowpea produced the highest amounts of aboveground biomass in the previous years (Martins et al, 2013) and probably also the highest amounts of belowground biomass. The decomposition of this biomass could increase the availability of mineral N, and it has been shown that high N availability reduces N fixation (Schipanski et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Soybeans can also meet their N needs from soil inorganic N pools. Because BNF is energy intensive (Silsbury 1977), soybeans are expected to favor inorganic N uptake when N availability in soil increases (Peoples et al 1995b;Schipanski et al 2010). This expectation for a changing contribution of BNF to the aboveground biomass has been tested in field studies.…”
Section: Introductionmentioning
confidence: 99%